Parenting Seminar as Strengthening Parental Communication Competence in the Digital Era - Isna Siskawati; Siti Munawaroh; Sita Nurfitriani; Aulia Rahma Putri (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2026)
The rapid development of digital technology presents fundamental challenges in child-rearing dynamics, particularly in parent-child communication in the digital era. This community service activity aims to enhance parents’ abilities in managing communication, parenting, and supervision of children’s gadget use. The program was implemented in Matagara Village, targeting parents struggling with screen time management, establishing gadget rules, and maintaining warm, empathetic, and constructive dialogue with their children. The method employed was Participatory Action Research (PAR), consisting of problem identification through Focus Group Discussions (FGD), intervention via a ±4-hour seminar “Parenting Communication in the Digital Era” using interactive lectures, case studies, group discussions, and Q&A sessions, and impact evaluation through pre-tests, participatory observation, and follow-up interviews. Results indicated improved parental communication competence in knowledge, attitudes, and skills. Before the seminar, most participants lacked understanding of digital parenting and did not have home gadget rules, whereas after the seminar, they began setting time limits, practicing dialogical two-way communication, and increasing open conversations with their children about digital activities. These findings confirm that community-based educational interventions through participatory parenting seminars effectively strengthen family capacity to develop adaptive parenting while supporting the growth of more resilient, digitally literate children.